Normal vitreous promotes angiogenesi via the epidermal growth factor receptor. Issue 11 (10th September 2020) - You, Mengling; Xia, Xiaobo; Li, Haibo; Wu, Jiayu; Rong, Rong; Zeng, Zhou; Xiong, Kun; Huang, Jufang; Tang, Luosheng; Lei, Hetian; Wu, Wenyi; Ji, Dan
Abstract: Vitreous, a transparent tissue in our body, contains anti‐angiogenesis factors. Our previous work reported that vitreous activates the signaling pathway of epidermal growth factor receptor (EGFR), which plays a critical role in angiogenesis. The aim of this study was to determine the role of EGFR in vitreous‐induced angiogenesis‐related cellular responses in vitro. Using a pharmacologic and molecular approach, we found that vitreous increased proliferation and migration via EGFR in human umbilical vein endothelial cells (HUVECs). Furthermore, we demonstrated that vitreous promoted tube formation via EGFR in HUVECs. Subsequently, depletion of EGFR using CRISPR/Cas9 and blockage with EGFR inhibitor AG1478 suppressed vitreous‐induced Akt activation and cell proliferation, migration, and tube formation in HUVECs. The significance of the angiogenic effect derived from vitreous demonstrates the importance of vitreous in the ocular physiology and the pathobiology of angiogenesis‐related ophthalmic diseases, such as proliferative diabetic retinopathy.